2013
DOI: 10.1105/tpc.113.111013
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of a Complex Locus for Terpene Biosynthesis in Solanum    

Abstract: Functional gene clusters, containing two or more genes encoding different enzymes for the same pathway, are sometimes observed in plant genomes, most often when the genes specify the synthesis of specialized defensive metabolites. Here, we show that a cluster of genes in tomato (Solanum lycopersicum; Solanaceae) contains genes for terpene synthases (TPSs) that specify the synthesis of monoterpenes and diterpenes from cis-prenyl diphosphates, substrates that are synthesized by enzymes encoded by cis-prenyl tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
157
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 141 publications
(159 citation statements)
references
References 47 publications
1
157
0
1
Order By: Relevance
“…The nearly ubiquitous presence of ZmAN2 as a pathogen defense transcript marker is consistent with the essential biosynthetic role in the modular formation of multiple specialized diterpenoid metabolites, including not only A-and B-series kauralexins but also dolabralexins. Notably, ZmAN2 does not cluster with any class I diTPSs in the maize genome, illustrating a different genomic organization of diterpenoid metabolism in maize as compared with rice and tomato (Solanum lycopersicum), where several specialized diterpenoid pathways form functional biosynthetic clusters (Matsuba et al, 2013;Nützmann et al, 2016). However, the presence of the uncharacterized class II diTPSs ZmCPS3 and ZmCPS4 suggests that specialized diterpenoid metabolism in maize likely follows the common modular blueprint of combining different diTPS and P450 enzymes, as shown for rice, wheat, and various other species across the plant kingdom (Xu et al, 2007a;Zhou et al, 2012;Hall et al, 2013;Cui et al, 2015;Zerbe and Bohlmann, 2015).…”
Section: Discussionmentioning
confidence: 97%
“…The nearly ubiquitous presence of ZmAN2 as a pathogen defense transcript marker is consistent with the essential biosynthetic role in the modular formation of multiple specialized diterpenoid metabolites, including not only A-and B-series kauralexins but also dolabralexins. Notably, ZmAN2 does not cluster with any class I diTPSs in the maize genome, illustrating a different genomic organization of diterpenoid metabolism in maize as compared with rice and tomato (Solanum lycopersicum), where several specialized diterpenoid pathways form functional biosynthetic clusters (Matsuba et al, 2013;Nützmann et al, 2016). However, the presence of the uncharacterized class II diTPSs ZmCPS3 and ZmCPS4 suggests that specialized diterpenoid metabolism in maize likely follows the common modular blueprint of combining different diTPS and P450 enzymes, as shown for rice, wheat, and various other species across the plant kingdom (Xu et al, 2007a;Zhou et al, 2012;Hall et al, 2013;Cui et al, 2015;Zerbe and Bohlmann, 2015).…”
Section: Discussionmentioning
confidence: 97%
“…Tissue-specific accumulation of metabolites, representing one of the main contributions to metabolite diversity, is of great interest to plant scientists (Schilmiller et al, 2010;Chan et al, 2011;Watanabe et al, 2013). Metabolic diversity between different tissues might arise from differences in spatial-temporal expression of genes (Kim et al, 2012;Thatcher et al, 2014) and in some cases by duplicate genes that display spatially or temporally distinct expression patterns (Toubiana et al, 2012;Matsuba et al, 2013). By comparing genetically controlled natural variation of PAs in different tissues at high resolution, we have shown that although coordinated genetic control across various tissues can be observed for some PAs, the majority of the loci were obtained in a tissue-specific manner (Supplemental Table 4), suggesting distinct regulation underlying the metabolic readout between tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms that underlie the evolution of specialized metabolism are diverse but frequently involve gene duplication or gene family expansion, coupled with subfunctionalization or neofunctionalization that may influence the expression pattern of a given gene or the activity of a protein or enzyme (Pichersky and Lewinsohn, 2011;Shoji and Hashimoto, 2011;Niemüller et al, 2012;Weng et al, 2012;Kaltenegger et al, 2013;Matsuba et al, 2013;Kang et al, 2014). Relative to Arabidopsis, there is an expansion of the ArAT gene family in A. belladonna, tomato, and potato, with two or three ArAT genes present in these species for each Arabidopsis gene (Figure 4).…”
Section: Discussionmentioning
confidence: 99%